An Inverse Problem of Textile Materials Determination under Low Temperature (Journal of Fiber Bioengineering and Informatics, 2018)
Based on the model of steady-state heat and moisture transfer through textiles, an Inverse Problem ofBilayer Textile Materials Determination (IPTMD) under low temperature is presented. According tothe idea of regularization method, the IPTMD can be formulated into a function minimization problem.Combining the finite difference algorithm for nonlinear ordinary differential equation with direct searchmethod of one-dimensional minimization problems, an iterative algorithm for the regularized solution ofthe inverse problem is constructed. By analyzing the results of numerical simulation of different climateclothing, some conclusions are obtained: Hooke-Jevees direct search method can solve the inverse problemof bilayer textile materials determination, numerical simulation also shows the effectiveness of algorithmand the rationality of the proposed inverse problem, most importantly, the results can give some scientificexplanations for experiments with the textile materials.